See me eaudiobook - Sparks, Nicholas (2015)
In this suspenseful New York Times bestseller, a chance encounter between a successful lawyer and a rebellious bad boy will change life as they know it forever, as their pasts catch up with them... Colin Hancock is giving his second chance his best shot. With a history of violence and bad decisions behind him and the threat of prison dogging his every step, he's determined to walk a straight line. To Colin, that means applying himself toward his teaching degree and avoiding everything that proved destructive in his earlier life. The last thing he is looking for is a serious relationship. Maria Sanchez, the hardworking daughter of Mexican immigrants, is the picture of conventional success. With a degree from Duke Law School and a job at a prestigious firm in Wilmington, she is a dark-haired beauty with a seemingly flawless professional track record. And yet Maria has a traumatic history of her own, one that compelled her to return to her hometown and left her questioning so much of what she once believed. A chance encounter on a rain-swept road will alter the course of both Colin and Maria's lives, challenging deeply held assumptions about each other and ultimately, themselves. As love unexpectedly takes hold between them, they dare to envision what a future together could possibly look like . . . until menacing reminders of events in Maria's past begin to surface. Rich in emotion and fueled with suspense, See Me reminds us that love is sometimes forged in the crises that threaten to shatter us . . . and those who see us for who we truly are may not always be easy to recognize.